Elaine Steinbeck at Grapes of Wrath 50th Anniversary Party - unknown:::Creator::::::::::::
Elaine Steinbeck (far right) with two unidentified men and a woman at The Grapes of Wrath 50th Anniversary celebration at the '21' Club on 21 West 52nd Street in New York City. This party was attended by Douglas Fairbanks, Junior; Elia Kazan; Arthur Schlesinger, Junior; Edward Albee; and Tom Guinzburg (son of Steinbeck's publisher).